IMPACT OF LOYALTY BARGAIN TO THE POLITICISATION OF THE PUBLIC SECTOR IN LITHUANIA - Kazakevičius, Giedrius (Politologija, 2014)
SummaryThis article deals with politicisation of the public sector in Lithuania in the context of ensuring loyalty of high public officials to the politics of the Government of the day. The theoretical framework of Public Service Bargains (PSBs) was used in order to analyse historical changes and contemporary perception of loyalty among politicians and high public officials. The analysis of available historical researches does not allow identifying precisely a clear picture of the loyalty bargain in the public sector of the interwar Lithuania. But the lack of clear legal framework, some elements of the tsarist Russia public administration tradition and no evidence on the intended attempt to create loyalty to the state and the law don’t allow regarding historical Lithuanian interwar tradition as a hierarchical loyalty bargain. Post-war Soviet type administration tradition in Lithuania was analysed taking into account the researches of central Soviet administration tradition as well as studies of the Soviet Lithuania administration. A close look at the dual type Soviet administration provides evidence on the domination of egalitarian with some individualistic elements loyalty bargain type among the ruling elite. This type of loyalty bargain was secured by a personal loyalty network based on formal and informal ties. An analysis of changes in the legislative framework after re-establishing independence was used to identify the attempts to redefine loyalty bargain in transition period. The integration to the EU was a factor that was used by the administrative elite of Lithuania to secure a hierarchical loyalty bargain in a formal and legalistic way without reaching a common understanding with politicians. This hierarchical loyalty bargain is not based on historical administrative or cultural tradition. An analysis of biographies of the heads of the policy making institutions, statements of politicians as well as courts’ decisions regarding the removal from office provides a mixed picture regarding the praxis of loyalty bargain in the Lithuanian public sector. There is some evidence that politicians prefer egalitarian loyalty bargain and do not recognise formal hierarchical loyalty setting. The hierarchical loyalty bargain is tolerated by politicians only with judges and in some cases with the heads of the regulatory agencies. On the other hand, most of the heads of the policy making institutions are making attempts to consolidate the hierarchical loyalty bargain through legal means. This situation could be regarded as cheating on loyalty bargain from both sides that provoke politicians to search for new ways in achieving the loyalty of high public officials to the politics of the incumbent government and exercise politicisation practices for that purpose